ANALISIS KESALAHAN MAHASISWA DALAM MENYELESAIKAN SOAL KESEIMBANGAN PASAR PADA MATA KULIAH MATEMATIKA KEUANGAN DAN BISNIS - Tuhfatul Janan; Ratna Damayanti; Abdur Rofiq (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This research aims to give the description about the mistakes by students in solving market balance problems in financial and business mathematics course. The method in this research is a qualitative descriptive method and the subjects in this research were semester 2 students of the Islamic Economics study program at STAI Muhammadiyah Probolinggo. The techniques for data collection are exams and interviews, while the technique for data analysis in this research uses the formula P=  f/N ×100%. Based on the results of the research, it was concluded that there were 5 errors by the subjects in solving market balance problems in financial and business mathematics course, namely errors in writing Q_s notation, doing the calculation process, moving numbers or variables from one segment to another, multiplying both sides with a number to eliminate the denominator on a side, and errors in determining the offered price after tax.